2009
DOI: 10.1016/j.vaccine.2009.09.106
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer immunotherapy yields superior long-term survival in TRAMP mice when administered at an early stage of carcinogenesis prior to the establishment of tumor-associated immunosuppression at later stages

Abstract: Prostate cancer immunotherapy clinical trials have been performed, but often in immunocompromised patients with limited clinical success. The study aim was to determine whether the stage of prostate cancer development at which immunization occurs affects vaccine efficacy, and if so which tumor-associated immunosuppressive mechanisms may be involved at later stages. Therapeutic vaccination of TRAMP mice with only precancerous PIN lesions confered superior protection than immunization after development of invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 31 publications
3
34
0
Order By: Relevance
“…1A). Notably, in line with the findings from previous studies (41,42), the development of prostate carcinoma in the TRAMP mice is also accompanied by increased expression of TGF-b1 in the prostate (Fig. 1, Supplemental Fig.…”
Section: Expression Of Tgf-b In Advanced Invasive Prostate Tumors Insupporting
confidence: 91%
“…1A). Notably, in line with the findings from previous studies (41,42), the development of prostate carcinoma in the TRAMP mice is also accompanied by increased expression of TGF-b1 in the prostate (Fig. 1, Supplemental Fig.…”
Section: Expression Of Tgf-b In Advanced Invasive Prostate Tumors Insupporting
confidence: 91%
“…No commercial formulations are available, particularly in prostate cancer, as the efficacy of the developed vaccines relies on the immunosuppressive state of the patients included in clinical trials and their tumor microenvironment, which prevents triggering of an immune response. Two studies that applied a mouse STEAP1 DNA prime/Venezuelan equine encephalitis virus-like replicon particles boost vaccine showed the efficacy of this therapeutic strategy against prostate cancer (73,80). The capacity of this vaccine to trigger an immune response could be seen by the increasing number of CD8 þ and CD4 þ T cells and by the production of cytokines such as TNF-a, IFN-a, IL-2, and IL-12 following vaccination of C57BL/6 mice injected with a cell line derived from the transgenic adenocarcinoma mouse model, TRAMPC-2 (73).…”
Section: Steap Proteins As Immunotherapeutic Targetsmentioning
confidence: 99%
“…Protection against prostate cancer dramatically increases when vaccination occurs in mice mimicking earlier stages of cancer. Immunosuppressive mechanisms that lead to a reduction of Th1 and Th2 function, reduction of proinflammatory cytokines, and increased expression of immunosuppressive factors activated during prostate cancer progression tend to interfere with the efficacy of the vaccine (80). Avoiding the establishment of an immunosuppressive tumor microenvironment seems, therefore, to be the key to the success of therapeutic vaccination in later cancer stages.…”
Section: Steap Proteins As Immunotherapeutic Targetsmentioning
confidence: 99%
“…Besides the effect of androgen deprivation therapy (ADT) on the progression of PCA by surgical castration of TRAMP mice [41,42], the effects of many agents with chemopreventive potential including green tea [26,43], NSAIDs [44,45], flutamide [46], retinoic acid [47], vitamin E analog [48], genistein [24,49], epigallocatechin-3-gallate (EGCG) [50], silibinin [23,51], dietary restriction [52] and immunotherapy [53,54], have been studied using this model. While most of the publications reported anti-cancer effects of their test compounds, El Touny et al showed that feeding TRAMP mice (TRAMP-FVB) with a diet containing 0.25% genistein from 12 to 20 WOA induced an aggressive progression of PCA, as evidenced by a 16% increase in the number of WD and PD prostates, coinciding with a 70% incidence of pelvic lymph node metastases as opposed to 0% in the control group [49].…”
Section: Effects Of Chemopreventive Agents On Prostate Carcinogenesismentioning
confidence: 99%